1990
DOI: 10.1007/bf01104141
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation and germination effects on phytate, protein and amino acids of soybean

Abstract: Influence of irradiation (0.05-0.20 kGy) and germination (24-120 hours) in distilled and tap water on phytate, protein and amino acids of soybean, was studied. Phytate values significantly decreased with increasing germination period and irradiation dose (P less than 0.01). Irradiation independently decreased the original phytate (212.0 mg/100 g) to a range value of 205.0-190.0 mg/100 g depending upon dose level. Germination of unirradiated seeds for 120 hours in distilled and tap water lowered the phytate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 30 publications
6
15
0
Order By: Relevance
“…The amino acid content for irradiated sample with 20 Gy was increased by 1.7 fold over that of control sample. The observed increase in total soluble amino acid content due to exposure to ionizing radiation is in agreement with findings by Satter et al (1990) who documented increases in essential and nonessential amino acids of soybean when irradiated at a dose level of 0.10 kGy. Also, Maity et al (2009) found that increase in total soluble amino acids content in irradiated edible seed at 6 kGy.…”
Section: Resultssupporting
confidence: 93%
“…The amino acid content for irradiated sample with 20 Gy was increased by 1.7 fold over that of control sample. The observed increase in total soluble amino acid content due to exposure to ionizing radiation is in agreement with findings by Satter et al (1990) who documented increases in essential and nonessential amino acids of soybean when irradiated at a dose level of 0.10 kGy. Also, Maity et al (2009) found that increase in total soluble amino acids content in irradiated edible seed at 6 kGy.…”
Section: Resultssupporting
confidence: 93%
“…Similar results have been reported elsewhere [15,26,27]. This increase may be due to a synthesis of enzyme proteins or a compositional change following the degradation of other constituents as carbohydrates [28].…”
Section: Effect Of Germination On Soybean Chemical Compositionsupporting
confidence: 88%
“…These include undesirable flavor and odor due to lipoxygenase activity and the presence of antinutritional factors such as trypsin inhibitors, phytates, and flatulent. Many studies showed the benefits of germinated soybeans, including improvement of nutritional quality by prevention of lipid oxidation, increase of the nutrients such as ascorbic acid and riboflavin contents, hydrolysis of raffinose and stachyose that are responsible for flatulence problems, and decrease of trypsin inhibitors [18][19][20][21]. However, limited information is available on the effect of soybean germination on isoflavone content and composition [22].…”
Section: Introductionmentioning
confidence: 99%